Ibn Hajar Al-’Asqalani: Biografi Seorang Tokoh Ilmu Hadis - Haji Suliaman, Ishak (Jurnal Usuluddin, 1998)
This article is an attempts to analyze the personality and contributions of Ibn Hajar al-’Asqalani, a hadith scholar, who lived in 8th century of Hijrah. This study is focused on his contributions and written works produced in the field of hadith.